ANALYSIS OF WORKING RISK OPERATION OF POLE AND LINE FISHING IN NORTH MALUKU WATERS - Ikhsan, Suci Asrina; Pramesthy, Tyas Dita; Tiku, Mathius; Arkham, Muhammad Nur; Hutapea, Roma Yuli F.; Ananda, Tuah (Politeknik Kelautan dan Perikanan Dumai, 2023)
Pole and line is one of the most dominant fishing tools at the Bitung Ocean Fishing Port. The aim of this research is to determine the risk of work accidents when operating pole and line fishing gear. The data used in the research was taken by direct observation in the field and using the HTA (Hierachical Task Analysis) method. This method is used to find out all the activity processes of a job, in order to know the sub-activities when operating pole and line fishing gear. The risk of work accidents that can occur when operating pole and line fishing equipment is in the low risk and medium risk categories. Activities that have low risk are 9 activities with a percentage of 75% including activities: 1) ship leaning against a floating chart, crew members walking on a floating chart, 2) putting fish (bait) into cans, 3) putting fish (bait) into hatch, 4) paying for bait, 5) crew turning on the water pump, 6) crew preparing for fishing, 7) watering caught fish, 8) putting fish into the hold, 9) giving ice to the fish. There are 3 medium risk activities with a percentage of 25%, the activities include: 1) buoys spreading live bait on the sea surface, 2) fishing line withdrawal, 3) fishing line lowering. There were no high risk activities found in the operation of pole and line fishing gear.